Development of a demand feeding system for brown-marbled grouper Epinephelus fuscoguttatus and orange-spotted grouper Epinephelus coioides juveniles - Tan, Nai Han (2013)
Demand feeding is a new feeding method by which fish can feed themselves. Fish switch on the feeding device when they require food. This method has several advantages because the fish can eat when they are most motivated to feed. The system can thus minimize feed loss and reduce water pollution. Before developing a suitable demand feeding device for groupers, fish circadian rhythms, visual acuity and visual axis were examined. Both brown-marbled grouper Epinephe/us fuscoguttatus and orange-spotted grouper Epinephelus coioides juveniles showed typical diurnal rhythms. The visual axis of brown-marbled grouper juveniles was forward while the visual axis of orange-spotted grouper juveniles was upward and forward. Based on these results, a rearing experiment was done to evaluate the efficiency of different feeding methods for brown-marbled grouper and orangespotted grouper juveniles. Three experimental groups, pendulum demand feeder group (PDF, FH221, Aquatic Eco-Systems, Inc.), infrared sensor demand feeder group (IRDF) and automatic feeder group (AF) were set with three replicates. The IRDF consisted of an infrared sensor (infra red light 950 nm) ending in a red pelletlike knob with food container. Both demand feeders (PDF and IRDF) were set to dispense 10-15 pellets when fish activated the trigger (pendulum rod and infrared sensor, respectively) located 2 cm below the water surface. The automatic feeder (AF) was set to dispense 150-170 pellets at 8:00 am and 4:00 pm. In the rearing experiment, ten juveniles were kept in a 500 L round polyethylene tank (nine tanks, 90 fish) with flow through water system and water exchange (90%) every morning. Throughout the experiment, fish were exposed to natural photoperiod. The experiment lasted for 25 days. Water temperature was 28.0 - 31.5 °C and salinity was 27-28 ppt. During rearing experiment, the fish were fed with pellets. Fish standard length (SL), total length (TL), body weight (BW), specific growth rates (SGR) and adjusted feed conversion ratio (FCRadj) were compared. In brownmarbled grouper, total length of IRDF group was significantly higher (P<0.05) than that of PDF group. SL and BW growth rates of three groups were not significantly different (P>0.05). In orange-spotted grouper, there were no significant differences (P>0.05), but SL, TL, and BW growth rates of IRDF group showed higher tendency than those of AF and PDF groups. SGR of IRDF group for both grouper species was higher tendency than that of AF and PDF groups. FCRadj was better in IRDF group. Therefore, IRDF demand feeding devices are considered suitable for juvenile rearing of groupers.